Making the Most of Demographic Change in Southern Africa - Ahmed, S. Amer (World Bank, Washington, DC, 2016)
The countries of the Southern African Customs Union have relatively diverse demographic and economic starting points. These economies have the potential to realize demographic dividends and experience an acceleration in their income per capita growth and poverty reduction progress through forthcoming shifts in their age structures. Between 35 and 75 percent of poverty reduction in 2015-50 in Southern African Customs Union economies could be attributed to demographic shifts in a business-as-usual scenario of economic development, if employment rates are at least maintained. The magnitude of the demographic dividends could be greater if countries are able to achieve policy outcomes in parallel in the areas of education, savings-investment, and employment. Scenario analyses of these different policy outcomes interacting with the shifting age structures in different ways suggest quantitatively different economic impacts despite qualitatively similar policies. Improving educational attainment is found to be most important in Lesotho and Swaziland; mobilizing savings for higher investment can be most useful for Botswana; and improving employment rates, especially by closing gender gaps, can be most useful for South Africa and Namibia.